2011
DOI: 10.1021/ol201303h
|View full text |Cite
|
Sign up to set email alerts
|

Perylene Anhydride Fused Porphyrins as Near-Infrared Sensitizers for Dye-Sensitized Solar Cells

Abstract: Two perylene anhydride fused porphyrins 1 and 2 have been synthesized and employed successfully in dye-sensitized solar cells (DSCs). Both compounds showed broad incident monochromatic photon-to-current conversion efficiency spectra covering the entire visible spectral region and even extending into the near-infrared (NIR) region up to 1000 nm, which is impressive for ruthenium-free dyes in DSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 37 publications
0
74
0
Order By: Relevance
“…125 In 2011, Ishida et al reported one of the best performing β-linked porphyrin dyes to date (tda-2b-bd-Zn) with a PCE of 7.5% ( Figure 9). 126,127 More recently, covalently linked porphyrin dimers 128−133 trimer/tryad, 134−136 π-elongated porphyrins 137 fused with naphthalene, 138 antracene, 139−142 perylene, 143 quinoxaline, 144−146 or porphyrin itself 128,147 (fused-porphyrin dimers) were reported as promising dyes featuring extended absorption in the visible (red) and NIR regions. Since 2009 and until now, meso-porphyrins have been the most efficient class of porphyrin sensitizers reported in DSSCs.…”
Section: Porphyrins For Dsscsmentioning
confidence: 99%
“…125 In 2011, Ishida et al reported one of the best performing β-linked porphyrin dyes to date (tda-2b-bd-Zn) with a PCE of 7.5% ( Figure 9). 126,127 More recently, covalently linked porphyrin dimers 128−133 trimer/tryad, 134−136 π-elongated porphyrins 137 fused with naphthalene, 138 antracene, 139−142 perylene, 143 quinoxaline, 144−146 or porphyrin itself 128,147 (fused-porphyrin dimers) were reported as promising dyes featuring extended absorption in the visible (red) and NIR regions. Since 2009 and until now, meso-porphyrins have been the most efficient class of porphyrin sensitizers reported in DSSCs.…”
Section: Porphyrins For Dsscsmentioning
confidence: 99%
“…Among the β-fused porphyrins, particular structures can be mentioned such as perylene fused porphyrins 240 and dimeric porphyrins, 241 in which more extended structures were used to improve the light harvesting efficiencies of the dye. In the case of the perylene fused Ni porphyrins of Figure 62, the low efficiencies values (η = 1.3%) were attributed to an aggregation of the dye facilitated by their planar structure.…”
Section: β β-Fused Porphyrinsmentioning
confidence: 99%
“…BODIPY M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 1 was synthesized in a yield of 45 % by reacting 2-methylpyrrole [18] with 1-naphthaldehyde in the presence of trifluoroacetic acid (TFA), followed by oxidation with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ). [19] BODIPY 2 was synthesized by oxidizing 1 with FeCl 3 with a yield of 31 %.…”
Section: Resultsmentioning
confidence: 99%